Klf4 Alleviates Lipopolysaccharide-Induced Inflammation by Inducing Expression of MCP-1 Induced Protein 1 to Deubiquitinate TRAF6 - Zhenzhen Li; Yanhui Jia; Shichao Han; Xingqin Wang; Fu Han; Julei Zhang; Wei Zhang; Hao Guan; Dahai Hu (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Inflammation is an essential component of innate immunity against pathogens, but is tightly regulated, such as by Krüppel-like factor 4 (Klf4), to prevent injury. Klf4 also regulates macrophage polarization, although the mechanisms underlying both functions are poorly understood. The aim of this study was to investigate whether and how Klf4 prevents unregulated inflammation. Methods: The bone marrow-derived macrophages and RAW264.7 cell line were used. Quantitative real-time PCR was used to determine inflammatory cytokines (IL-1β, TNF-α, IL-6 and MCP-1), Klf4 and MCPIP1 transcript levels. Extraction of nuclear and cytoplasmic proteins and Immunoblotting were used to determine Klf4, MCPIP1, relative kinases from NF-κB pathway and K63-linked polyubiquitins expression in nucleus and cytoplasm separately. Dual luciferase reporter assay was used to analyze whether Klf4 mediate MCPIP1 transcription. Immunoprecipitation was used to determine the protein interaction among Klf4, MCPIP1, TRAF6 and K63-linked polyubiquitins. Secretion of IL-1β and TNF-α into sera in mice was measured by Enzyme-linked immunosorbent assay. Results: We found that exposure to lipopolysaccharides suppresses Klf4 expression, even as it induces release of pro-inflammatory cytokines. Strikingly, Klf4 overexpression significantly lowered cytokine secretion and NF-κB signaling in the cytoplasm following exposure to lipopolysaccharide, even though Klf4 was exclusively nuclear. The cytoplasmic effects are likely mediated by MCP-1 induced protein 1 (MCPIP1), a deubiquitinase and a key modulator of inflammation that accumulates both in the nucleus and cytoplasm in response to Klf4. Indeed, binding between MCPIP1 and K63 polyubiquitins is attenuated in macrophages overexpressing Klf4, suggesting that MCPIP1 is an intermediator induced by Klf4 in the nucleus to remove K63 polyubiquitins from TRAF6 in the cytoplasm, and thereby impede NF-κB and inflammatory signaling. Importantly, Klf4 overexpression in mice alleviated sepsis symptoms following exposure to lipopolysaccharides. Conclusion: The data highlight Klf4 as an essential MCPIP1-dependent modulator of innate immunity that protects against excessive and self-destructive inflammation.